THREE ATTITUDE MODELS ON THE USE OF QR CODE IN EFL INDEPENDENT LEARNING AT CORDOVA ELEMENTARY SCHOOL - Evi Wulandhari; Susilo; Aridah (English Department, Faculty of Teacher Training and Education, Mulawarman University, 2024)
This research was about three attitude models on the use of QR Code in EFL independent learning at Cordova elementary school. The design of this study was qualitative phenomenology. This study use semi-structured interview from four selected students to collect the data. Participants were selected using purposive sampling with the criteria that had been prepared by the researcher. This research aimed to find out three attitude models based on Spooncer (1992) theory, the occurred of students feeling, beliefs, and behaviours. First, the students feelings there were two main points advantages and attractiveness. Advantages regards to ease and learning media. Attractiveness regards to interesting and fun. Secondly, the students beliefs there were two main points improve ability and preferences. Improve ability regards to soft skill and hard skill. Preferences regards to agreements of students. Last, the students behave there were one main point about experiences of students. The Experiences regards to problems of media, problems of tools, and personality problems. Therefore, it is suggested that teachers will try to implement digital-based learning in schools and facilitate students with the internet and media.